Primary antibody deficiencies in Turkey: Molecular and clinical aspects - Fırtına, Sinem; Ng, Yuk Yin; Ng, Özden Hatırnaz; Kıykım, Ayça; Yücel Özek, Esra; Kara, Manolya; Aydıner, Elif; Nepesov, Serdar; Camcıoğlu, Yıldız; Sayar, Esra Hazar; Güngören, Ezgi Yalçın; Reisli, İsmail; et al. (Humana Press Inc, 2022)
Primary antibody deficiencies (PAD) are the most common subtype of primary immunodeficiencies, characterized by increased susceptibility to infections and autoimmunity, allergy, or malignancy predisposition. PAD syndromes comprise of immune system genes highlighted the key role of B cell activation, proliferation, migration, somatic hypermutation, or isotype switching have a wide spectrum from agammaglobulinemia to selective Ig deficiency. In this study, we describe the molecular and the clinical aspects of fifty-two PAD patients. The most common symptoms of our cohort were upper and lower respiratory infections, bronchiectasis, diarrhea, and recurrent fever. Almost all patients (98%) had at least one of the symptoms like autoimmunity, lymphoproliferation, allergy, or gastrointestinal disease. A custom-made next-generation sequencing (NGS) panel, which contains 24 genes, was designed to identify well-known disease-causing variants in our cohort. We identified eight variants (15.4%) among 52 PAD patients. The variants mapped to BTK (n = 4), CD40L (n = 1), ICOS (n = 1), IGHM (n = 1), and TCF3 (n = 1) genes. Three novel variants were described in the BTK (p.G414W), ICOS (p.G60*), and IGHM (p.S19*) genes. We performed Sanger sequencing to validate pathogenic variants and check for allelic segregation in the family. Targeted NGS panel sequencing can be beneficial as a suitable diagnostic modality for diagnosing well-known monogenic PAD diseases (only 2-10% of PADs); however, screening only the coding regions of the genome may not be adequately powered to solve the pathogenesis of PAD in all cases. Deciphering the regulatory regions of the genome and better understanding the epigenetic modifications will elucidate the molecular basis of complex PADs.
Keywords: Primary Antibody Deficiencies; Common Variable Immune Deficiency; Targeted Next-Generation Sequencing